Nicotina previne comportamento ansiogênico em peixe-zebra (Danio rerio) - Duarte, Tâmie (2019)
Exacerbated anxiety is a common neurobehavioral disorder, which can be modulated using anxiolytic compounds. Nicotine has a wide variety of effects on the central nervous system influencing various physiological parameters and behavioral functions. Due to its genetic ability, evolutionarily conserved neurotransmitters and extensive behavioral repertoire, the zebrafish (Danio rerio) has emerged as an useful model organism in psychopharmacological research. Because understanding the anxiolytic character of nicotine help elucidate therapeutic targets for treating anxiety, this work is limited to focusing on the observation of the anxiogenic behavior of zebrafish when exposed to an aversive situation (using the alarm substance) to analyze whether acute nicotine pretreatment can block and/or minimize these effects. For this purpose, the fish were individually exposed to 1 mg/L nicotine or non-chlorinated water for 3 min and then transferred to other tanks in the absence or presence of 3.5 mL/L alarm substance for 5 min. The behavior of fish was tested using the novel tank diving and light-dark tests. As expected, alarm substance triggered aversive behaviors by increasing the permanence in the bottom, freezing, erratic movements, scototaxis, and risk assessment episodes. Nicotine alone triggered anxiolytic behaviors by increasing the time spent in top area and the average duration of entry into the lit compartment. Furthermore, nicotine prevented alarm substance-induced aversive responses in both tests. Overall, these results show the beneficial effects of nicotine on the ansiogenic responses of zebrafish.